Effect of the Predict-Observe-Explain (POE) Strategy on Achievement in Science Education: A Meta-Analysis Study - Zeynep Koyunlu Ünlü (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
Predict-observe-explain (POE) is a strategy that has been used in science education for several decades. It is important to determine how effective this strategy is, especially when used in the constructing scientific concepts. In this study, the effect of the POE strategy on students’ science achievement was examined in a meta-analysis. Databases were searched using specific keywords and 35 studies (6 theses and 29 articles) that met the inclusion criteria were found. Hedges’ g and the random effects model were used to calculate effect sizes. As a result, the average effect size (g=0.979, 95% CI: 0.771-1.188, p